Male Fertility: Review of the Publications of October – December 2019 - D. S. Rogozin (Вестник урологии)
The article provides an overview of the most influential papers on the topic of «male infertility». The main selection criteria were the practical significance of the article and the impact factor of the journal in which it was published, according to SCImago Journal Rank (SJR). As a result, we created the list of 10 papers published in the IV quarter (October − December) of 2019. The review included articles on the following issues: the effectiveness and prognostic factors of the effectiveness of microsurgical testicular sperm extraction (micro-TESE), the significance of sperm DNA fragmentation and «advanced paternal age» in the effectiveness of assisted reproduction technologies (ART) procedures, the role of latent chlamydial infection in azoospermia, management of adolescents with Kleinfelter syndrome, the effectiveness and safety of aromatase inhibitors in treatment of male infertility, sperm microbiome, the association between ART procedures and the cancer risk in children, follicle-stimulating hormone (FSH) treatment of male idiopathic infertility.